Mapeamento dos riscos psicossociais relacionados ao trabalho em profissionais da Diretoria de Vigilância em Saúde do município de Palmas – TO - Sousa, Nadja de Oliveira Figueiredo de (Universidade Federal do Tocantins, 2016)
Labor organizations undergo continuous transformations that require complex restructuring of the relationship between work and health, which should be understood as a determining factor for the quality of work and organizational success. Thus, promotion and prevention to workers' health need to be experienced in the Institution and intermediated by a team of people who will promote health actions. Based on this assumption, there is an identified need to work toward the health of the public servants of the Board of Health Surveillance (DVS), whose role is being a constant observer of the population’s health, aware of stress and other factors that can lead to illness. In this context, the present study aims to map out the psychosocial risks in the work of servants of the Board of Health Surveillance in the city of Palmas-TO. Specifically, we sought to investigate the characteristics of the prescribed work organization in the DVS; evaluate the management style of work organization in the respective body; identify the risk of pathogenic suffering at work by a group of public servants in healthcare; identify the physical and psychosocial damage resulting from work in that body; and identify preventive and curative actions developed within this body. This is a social research of exploratory and descriptive nature, with the employment of quantitative and qualitative methods. The participants were DVS workers in all the management positions that make up the Board: 137 workers that account for 37% of the total servants. The Assessment Protocol for the Management of Psychosocial Risk at Work (PROART) was used for data collection sent via Google Docs. After calculating the simple random sample, we obtained 104 responses considered a valid sample. The quantitative data were analyzed with SPSS and the qualitative data through content analysis. The survey results indicate that the health of workers in this Institution is still feeble regarding the implementation of promotion and prevention actions. The DVS was characterized by presenting a group of professionals aware of the problems in the Institution and awaiting the dialogue between them and managers for transformation of the negative aspects of work. The bureaucratic management style strongly characterizes the Institution although the collective management style is also significantly representative. It was in the light of the Psychodynamics of Work that risks associated with both pathogenic suffering and ethical and creative suffering were identified. Risks that should undergo intervention by the management and the worker’s health team aiming at these servants’ health.